Which factors drive the decision to boycott and opt out of research rankings? - Michael Berlemann; Justus Haucap (Center for Economic Studies and ifo Institute (CESifo), 2012)
This note contains an empirical analysis of the decision of German-speaking business scholars to boycott and opt out of the best known research ranking of business scholars, initiated and published by Germany's largest business daily, Handelsblatt. Our analysis indicates that scientists who are more senior (already have a longer academic career) and scientists who have been either less successful or less eager to publish their research in internationally well renown journals with high impact factors are more likely to boycott the research ranking. In addition, scientists who have already been appointed to a professorship are more likely to boycott the ranking, while academics having obtained a Ph.D. (instead of a German-style doctorate) are less prone to supporting the boycott. Finally, researchers specializing in various more quantitatively oriented subjects (such as finance and operations research) are less likely to boycott the ranking, while researchers in some less quantitatively oriented subjects (such as business organization) are more likely supporting the boycott.
Keywords: I23; 330; research rankings; Handelsblatt; business administration